The Odyssey of science: The case of Karl Popper and Adolfo Figueroa - Figueroa, Adolfo Ivan (2023)
What does the Immanuel kant´s paradox mean for science? Why is the difference between analytic and synthetic sentences-propositions a central puzzle in science, epistemology, analytical philosophy, and philosophy of science? These inquiries entail a profound research on the foundation of philosophy and science. Despite all this necessary endeavor, this brief article focuses on the case Popper-Figueroa with the purpose to highlight the basic philosophical challenges regarding the construction of the bedrock - the substantiality of ontology- or the substratum in the scientific process.